L’humanisation des hybrides mi‑hommes, mi‑bêtes en question(s) - Jacqueline Leclercq-Marx (Frontière·s)
The present article examines the porosity of the boundaries between certain human-animal hybrids on the basis of the relatively intense cultural pressures directed at them that were evident between Antiquity and the Middle Ages. These cultural pressures, however, are less common among other creatures of the same general type. Might or might not there be a cultural predisposition to reinforce the more human aspect of monsters, which are already so highly anthropomorphized?Having raised questions about the general concept of humanization with regard to half-human and half-animal creatures, we will examine it in some Western texts written in the historical period roughly between the ninth and fifteenth centuries to see if these hybrids have already benefited from humanization in one form or another in the past. The creatures in question are five different hybrids of mythology and fabulous natural history: sirens (uniquely in their aspect of fish women), centaurs, cynocephali or dog heads, and satyrs or half-man half-goat.Finally, we will ask whether there is a determining cultural factor that has favoured this kind of particularly transgressive slippage between human and animal boundaries, even if it has not always and in case every instance prevailed.